1929
DOI: 10.1084/jem.50.5.673
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Vaccinal Immunity in Tissue Cultures

Abstract: Normal corneas inoculated in vitro with vaccine virus and then cultivated in antivaccinal plasma developed typical vaccinal lesions associated with Guarnieri bodies. In such cultures, after an incubation period of 24 or 48 hours, active vaccine virus was demonstrated by means of appropriate methods. Immune corneas inoculated in vitro with vaccine virus and then cultivated in normal or in antivaccinal plasma revealed either very mild vaccinal lesions or none at all. In some of the cultures after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1932
1932
1954
1954

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Similar observations have been reported for other viruses, for example, foot-and-mouth disease (3) and poliomyelitis (4)(5)(6). The possibility of infecting immune animal tissues in vitro with a variety of viruses, e.g., virus III (7), vaccinia (8), herpes simplex (9), the salivary gland virus of guinea pigs (10), and pseudorabies (11), does not necessarily weigh against this conception of the mechanism of antiviral immunity. The washing and soaking of the tissue fragments, which usually preceded the infection in such experiments, may have removed an antiviral substance that was fixed in the tissues or rendered it ineffec-five by dilution.…”
Section: Discussionsupporting
confidence: 71%
“…Similar observations have been reported for other viruses, for example, foot-and-mouth disease (3) and poliomyelitis (4)(5)(6). The possibility of infecting immune animal tissues in vitro with a variety of viruses, e.g., virus III (7), vaccinia (8), herpes simplex (9), the salivary gland virus of guinea pigs (10), and pseudorabies (11), does not necessarily weigh against this conception of the mechanism of antiviral immunity. The washing and soaking of the tissue fragments, which usually preceded the infection in such experiments, may have removed an antiviral substance that was fixed in the tissues or rendered it ineffec-five by dilution.…”
Section: Discussionsupporting
confidence: 71%
“…Here again, one must consider the role of variation in the inbred rat strain from which the original cells were derived and which now may be resistant to transplantation. This strain, T-333, differs in many ways from its specific normal prototype 14p as described earlier.B Its high susceptibility to EEE virus is shown in FIGURES 11,13,and 14. This result points to the need for more evidence on the comparative susceptibility to viruses of malignant cells and their specific normal prototypes. In fact, we have emphasized for many years the importance of creating and working with isogenic pairs of normal and malignant cells.…”
Section: Annals New York Academy Of Sciencesmentioning
confidence: 98%
“…This appears to be a legitimate conclusion from the results obtained by these observers but, in view of the fact that we find that the union of vaccinia virus with the cell in the living animal, as shown by the appearance of protection from the lethal photodynamic action of methylene blue, requires a minimum contact of 10^ hours, and as Rous, McMaster, and Hudack only allowed a contact of from one-quarter to 1 hour, we are inclined to believe that they were dealing rather with the action of immune serum on an adsorbed virus and that their results, while of the greatest interest from that point of view, do not concern our immediate problem here. This criticism also applies to the work of Rivers, Haagen, and Muckenfuss (1929) on the protection of the virus of vaccinia from the action of antivaccinial serum. Haagen (1933) found that the virus of yellow fever is quickly neutralized in vitro by immune serum in the presence of living cells of fowl embryo but that, if the virus is allowed to remain in contact with the cell for 3 hours at room temperature before the addition of the immune serum, the virus survives and multiplies in the tissue cultures.…”
Section: Discussionmentioning
confidence: 99%